UPDATING OF THE TAX LAW AS THE MAIN CONDITION OF DEVELOPMENT OF FISCAL SYSTEM OF THE STATE (ON THE EXAMPLE OF INCOME TAX OF THE ORGANIZATIONS) - Violetta Roschupkina (Вестник Северо-Кавказского федерального университета)
In article the review of the current legislation on income tax of the organizations is given, the critical analysis of existing rules of the tax law is made. The developed contradictions in regulation of income tax of the organizations, its incentivization, including, at the level of the subject of federation are specified, namely, Stavropol region, provisions on development and updating of the fiscal legislation are stated. The directions of tax regulation, since 2012 and to the present are critically investigated, the directions of its improvement are developed.